IMPLEMENTASI PROGRAM KEBERSIHAN LINGKUNGAN HIDUP OLEH DINAS LINGKUNGAN HIDUP KOTA SAMARINDA - La Pini (ADMINISTRASI PUBLIK, 2020)
The purpose of this study is to describe and analyze the implementation of the environmental cleanliness program by the Samarinda City Environmental Service and to describe and analyze the supporting and inhibiting factors for the implementation of the environmental cleanliness program by the Environmental Office of Samarinda City.This type of research used by researchers is a qualitative descriptive research type. Informants include key informants, namely the Head of Garbage and Hazardous Waste Management, the Environmental Office of Samarinda City. The supporting informants selected in this study were staff of the Samarinda City Environmental Service and the people of Samarinda City totaling 5 people. The data analysis used in this study is a qualitative data analysis method. Based on the results of the analysis and discussion, it is known that the Samarinda City Environmental Service provides cleaning equipment and equipment for field officers, provides solid waste operational facilities, for street sweepers in the form of trash cans on the side of the road, providing maintenance of solid waste infrastructure, supervising the management of solid waste. Kota Samarinda, which has carried out law enforcement / justice operations activities, is spread across Kota Samarinda 4 times a year, no socialization of solid waste management policies has been carried out. To date, the procurement of organic waste chopping machines at the Environmental Office of Samarinda City has not yet been implemented. The infrastructure and supporting facilities for the TPA in Samarinda City are complete.